A Commentary on “Association Between Oral Behaviors and Painful Temporomandibular Disorders: A Cross-Sectional Study in the General Population” [Response to Letter] - Zhang S; Sun R; Si J; Xiong X (Journal of Pain Research)
Shuyuan Zhang,1 Ruonan Sun,1 Jiarui Si,2 Xin Xiong2 1West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2Department of Orthodontics, West China Hospital of Stomatology, Sichuan University, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Xin Xiong, West China Hospital of Stomatology, Sichuan University, No. 14 section 3, Renmin South Road, Chengdu, 610041, People’s Republic of China, Tel/Fax +86-28-85503898, Email drxiongxin@scu.edu.cn